Pengaruh Pemberian Vermikompos pada Media Tanam Terhadap Efektivitas Gliocladium sp. dalam Mengendalikan Penyakit Layu Fusarium (Fusarium oxysporum) pada Tanaman Semangka (Citrulus vulgaris, Schard) - Winda Ruliyanti; Abdul Majid (Fakultas Pertanian Universitas Jember, 2020)
Watermelon is one of the plants that have good prospects and has high economic value, but its production is currently experiencing a decline. Decreased production caused by the pathogen Fusarium oxysporum which causes fusarium wilt disease in plants. losses caused by fusarium wilt attacks reach 20-30%. Utilization of Gliocladium sp. and vermicompost is an alternative step in controlling fusarium wilt. The results showed that the use of Gliocladium sp. and vermicompost can suppress the development of fusarium wilt disease. The use of Gliocladium sp. and vermicompost 250 grams/polybag can suppress the attack of fusarium wilt disease with a percentage of suppression of the incidence of disease by 70% and suppress the severity of the disease by 38.5% compared to controls. and has a control effectiveness value of 73.68% which is categorized very well. The use of Gliocladium sp. and vermicompost also affect plant growth and production.